El diseño editorial como apoyo a las terapias de estimulación visual en niños de 5 a 10 años con insuficiencia de convergencia de la óptica Ambato. - Hoyos Lozada, Johnny Alejandro (2024)
The use of editorial design in creating materials for visual stimulation, focused on convergence insufficiency, helps children with this visual condition that affects their ability to work together when focusing on nearby objects. Therefore, this research focuses on editorial design as support for visual stimulation therapies in children aged 5 to 10 years with convergence insufficiency at Optica Ambato. The general objective is to develop editorial materials for visual stimulation for children with convergence insufficiency who receive care at Optica Ambato. For this purpose, deductive, descriptive, exploratory, and explanatory methods with a mixed approach were used, applying field research through interviews. The sample consisted of 10 children who are patients at Optica Ambato, allowing for direct information to be obtained to address the problem and serve as a basis for designing editorial materials with defined characteristics, from ophthalmological properties to motivating the child audience. As a result, a proposal was made that took into account the requirements and specifications of the users, enabling the design of fusion cards for visual therapies. This not only meets the needs of children with convergence insufficiency but also complements therapeutic activities.